BUSCO: assessing genome assembly and annotation completeness with single-copy orthologs - Simão, Felipe A.; Waterhouse, Robert M.; Ioannidis, Panagiotis; Kriventseva, Evgenia V.; Zdobnov, Evgeny M. (Bioinformatics, 2015)
Motivation: Genomics has revolutionized biological research, but quality assessment of the resulting assembled sequences is complicated and remains mostly limited to technical measures like N50. Results: We propose a measure for quantitative assessment of genome assembly and annotation completeness based on evolutionarily informed expectations of gene content. We implemented the assessment procedure in open-source software, with sets of Benchmarking Universal Single-Copy Orthologs, named BUSCO. Availability and implementation: Software implemented in Python and datasets available for download from http://busco.ezlab.org. Contact:  evgeny.zdobnov@unige.ch Supplementary information:  Supplementary data are available at Bioinformatics online.